Nghiên cứu chế tạo cao su xốp trên cơ sở cao su tự nhiên sử dụng chất tạo xốp dạng chất chủ. Phần 1. Chế tạo và đặc trưng của chất tạo xốp dạng chất chủ. - Hưng, Đặng Việt; Dương, Đoàn Đắc; Chương, Bùi (Vietnam Journal of Chemistry, 2016)
Thermal decomposition of azodicarbonamide (ADC) was studied by TGA, DTG, DSC and volume of generated gases. Decomposition temperature of ADC which is predispered in rubber matrix dropped from 210 oC to 178 oC. Moreover, a zinc activator lowers the decomposition temperature to 165 oC. Decomposition temperature of the chemical blowing agent is more suitable for vulcanization of natural rubber. In the presence of the activator, pore density is higher and the cell distribution is more uniform. Thermal decomposition of azodicarbonamide was strongly affected by the rubber matrix, temperature and heating rate. Keywords. Natural rubber Foam, Blowing agent, Masterbatch, Predispered compound, Azodicarbonamide ADC.